2012
DOI: 10.1002/hed.23112
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of risk factors for retropharyngeal lymph node metastasis in carcinoma of the hypopharynx

Abstract: Our findings demonstrated that primary carcinoma subsites and multiple metastatic cervical lymph nodes are the principal risk factors for RPLN metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 20 publications
4
24
0
Order By: Relevance
“…These findings suggest that bilateral RPLN dissection should be considered in the locally advanced HPC extending to the contralateral side. In accordance with previous report, 16 RPLN metastasis was the most common in 25 of posterior cancer, but was also observed in 20% of postcricoid cancer and 11.3% of pyriform sinus cancer. By statistical analysis using chi-square test, presence of 3 or more pathological metastatic LN, level II pathological LN metastasis and bilateral pathological LN metastasis were significantly correlated with RPLN metastasis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings suggest that bilateral RPLN dissection should be considered in the locally advanced HPC extending to the contralateral side. In accordance with previous report, 16 RPLN metastasis was the most common in 25 of posterior cancer, but was also observed in 20% of postcricoid cancer and 11.3% of pyriform sinus cancer. By statistical analysis using chi-square test, presence of 3 or more pathological metastatic LN, level II pathological LN metastasis and bilateral pathological LN metastasis were significantly correlated with RPLN metastasis.…”
Section: Discussionsupporting
confidence: 92%
“…Involvement of RPLN is relatively rare in HPC patients, but could result in a cause of death . Reported rates of RPLN metastasis ranged from 14% to 19%, in accordance with our study (16.3%). As previously reported, preoperative FDG‐PET/CT scan was useful to evaluate RPLN in our study.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, three patients (50.0%) occured nodal failure at level II in contralateral or bilateral necks for patients not receiving adjuvant radiation therapy, which was much higher than patients who recevive postoperative RT (50.0% vs. 2.5%, P < 0.001; OR = 0.026, 95%CI: 0.002-0.328). Based on results found in our study, irradiation of the level VIb and VII should be recommended, especially for the primary tumors originated from posterior pharyngeal wall (PPW), PPW invasion, postcricoid invasion, and esophagus invasion [22,23].…”
Section: Discussionmentioning
confidence: 84%
“…Previous studies had indicated the incidence of RPLN of HPC was 20–62%. Su et al 10 found out the incidence of RPLN metastasis in HPC from 218 patients was 17.0%, and the highest rate of 36.4% was found in posterior pharyngeal wall tumor, mainly based on CT. Our study had a higher rate of RPLN metastasis (21.5%) and primary tumor located in posterior pharyngeal wall (53.1%).…”
Section: Discussionmentioning
confidence: 99%
“…There were a few studies in the early years showed that the risk factor of RPLN may be related to T stage, N stage, or the numbers of nodes. 12 , 15 Su et al 10 demonstrated that the primary tumor subsites, bilateral cervical LN metastasis, the number and size of cervical LNs, and level V metastasis were significantly associated with RPLN metastasis. The incidence of RPLN is higher in patients with LN metastasis in other cervical regions.…”
Section: Discussionmentioning
confidence: 99%